Nicotinic Acetylcholine Receptor α7 Subunit Is an Essential Regulator of Seizure Susceptibility - Sun, Peng; Liu, Da-Gang; Ye, Xiang-Ming (Frontiers in Neurology, 2021)
A large body of data has confirmed that α7 nicotinic acetylcholine receptors (nAChRs) play a pivotal role in cognition, memory, and other neuropsychiatric diseases, but their effect on seizure susceptibility in C57BL/6 wild-type mice is not fully understood. Here, we showed that decreased activity of α7 nAChRs could increase the excitability of CA1 pyramidal neurons and shorten the onset time of epilepsy in pilocarpine-induced mouse models. However, compared with the control group, there was no apparent effect of increasing the activity of α7 nAChRs. Moreover, the expression of α7 nAChRs is downregulated in human epileptogenic tissues. Taken together, our findings indicate that α7 nAChR is an essential regulator of seizure susceptibility.